2019
DOI: 10.1155/2019/2761427
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Interarch Tooth Size Relationship in Nepalese Subjects with Normal Occlusion and Malocclusions

Abstract: Introduction A proportional relationship between the maxillary and mandibular teeth size is required for achieving good finish with proper overjet and overbite postorthodontic treatment. The aims and objectives of this study were to determine the anterior and overall Bolton's ratio in Nepalese population, to compare Bolton's ratio between subjects with normal occlusion, Class I malocclusion, and Class II malocclusion, to compare these results with Bolton's norm, and to determine the frequency of clinically sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…This is in accordance to the study done by O' Mahony et al 22 and Uysal and Sari 7 . This is also in accordance to study done by Mishra et al 20 in Nepalese population who compared the tooth size discrepancies in normal occlusion, Class I malocclusion and Class II malocclusion groups. Our study showed that there was no difference in both anterior and overall ratio as compared between males and females (Table 3).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in accordance to the study done by O' Mahony et al 22 and Uysal and Sari 7 . This is also in accordance to study done by Mishra et al 20 in Nepalese population who compared the tooth size discrepancies in normal occlusion, Class I malocclusion and Class II malocclusion groups. Our study showed that there was no difference in both anterior and overall ratio as compared between males and females (Table 3).…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that there was no difference in both anterior and overall ratio as compared between males and females (Table 3). This is in agreement with the study done by Mishra et al 20 and Hong et al 23 in Nepalese population, M.A Ismail et al 24 and Mahmound NM et al 4 in Sudanese population, Endo et al 25 in Japanese population. This finding is in contrary to the study done in Nepalese population by Jaiswal A et al 26 They found the males have significantly higher anterior ratio as compared to females.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The presence of (TSD) should be identified during the initial diagnosis and treatment planning stage. Thus appropriate mechanisms can be applied for resolving the discrepancy [7]. The treatment alternatives for tooth-size discrepancies include the restoration of relatively small teeth, interproximal stripping of relatively large teeth, modification of crown angulations or inclination, and extraction [4].…”
Section: Introductionmentioning
confidence: 99%
“…The perfect percentage of the upper and lower tooth material had been suggested by several studies [7][8][9][10]. Among these, Bolton's ratios are the most usually used methods to decide inter-arch (TSD) in orthodontic patients [11].…”
Section: Introductionmentioning
confidence: 99%